E-commerce platform market share measurement mechanisms in Indonesian competition law: The urgency in digital era - Reni Budi Setianingrum; Muhammad Annas (Universitas Ahmad Dahlan, 2026)
Introduction to the Problem: Nowadays, Indonesia is the largest online shopping market in Southeast Asia, which is dominated by the two largest e-commerce platforms, namely Shopee and Tokopedia. The current concern is the emergence of market domination which could result in abuse of dominant position in the form of entry barriers for new players to enter and compete. An appropriate market share measurement method will help authorities prevent market dominance abuse and enforce competition law by imposing appropriate sanctions in the e-commerce sector Purpose/Study Objectives: This research aims to analyze the practice for measuring market share in the e-commerce sector regulated by the Indonesian Competition Commission (ICC) by taking lessons from the European Union Competition Law. Design/Methodology/Approach: This research is normative juridical research using a conceptual approach, statutory approach and comparative approach with an analytical descriptive method. Findings: ICC, as the enforcer of competition law in Indonesia, still uses the traditional market measurement method, namely the SSNIP test, which is considered no longer relevant to the digital economy market and has not implemented a special approach for measuring digital market share, including e-commerce. This study introduces a novel, context-specific framework for assessing digital market dominance in Indonesia by adapting the European Union’s SSNDQ principle, an approach that has not previously been applied within the Indonesian competition law regime. Paper Type: Research Article